Improved hemostasis with plasma kinetic bipolar sealing device in the vaginal steps of laparoscopic-assisted vaginal hysterectomy - Yi-An Tu; Wen-Chun Chang; Chin-Jui Wu; Bor-Ching Sheu (Elsevier, 2019)
Objective: During the vaginal steps of laparoscopic-assisted vaginal hysterectomy (LAVH), excessive bleeding occurs if the vascular pedicles are not securely clamped. Accordingly, this study investigates if an advanced bipolar sealing device (PlasmaKinetics [PK] Sealer), compared to conventional sutures, could improve the efficacy and safety in the vaginal steps of LAVH. Material and methods: The medical records of 101 women who underwent LAVH for a non-malignant condition between June 2014 and August 2017 were retrospectively reviewed. Among the women, 60 received LAVH using conventional sutures (control group), while 41 using the PK Sealer during vaginal steps (PK group). Results: A 35% reduction (76.1 vs. 117.3 mL) in the blood loss was observed in the PK group. The natural logarithm (ln) of the blood loss was significantly lower in the PK group than in the control group (P = .045). The percentage of cases which achieved the minimal blood loss goal (<50 mL) was significantly higher in the PK group than in the control group (61 vs. 48%, P = .044). After adjusting for confounding factors, the PK group still exhibited a significantly lower ln intraoperative blood loss (OR -0.477, P = .002) than the control group. Conclusion: The PK bipolar sealing device provides a safe and effective alternative in reducing blood loss in the vaginal steps of LAVH. Keywords: Bipolar coagulation, Laparoscopy, Hysterectomy